The Simulation of 3-Phase 17-Level Inverter Using Two Cascaded Square Wave Bridge - Basit, Abdul; Khan, Sheharyar; Wahab, Abdul; jalal, Kamil; Gohar, Waseem; Hussain, Kashif (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Nowadays, electronic devices are very sensible with harmonics. The need for a harmonic free and large-grade power supply is also enhanced to meet the industry’s requirements. This paper presents simulation of 3-phase 17-level cascaded h-bridge inverter by using two cascaded square wave bridge. Inverters are mainly divided as single or multi-level. The multi-level fundamental switching technique is used to control the power required for electronic switches. We have presented the methodology where switching angles are calculated so that the desired fundamental sinusoidal voltage is generated from the dc sources; however, at the same time, specific high order harmonics are removed. Comparative study of different types of sinusoidal pulse width modulation (SPWM) schemes such as phase disposition (PD), phase opposition disposition (POD) and alternative phase opposition disposition (APOD) with different modulation index (Ma) are proposed to decrease total harmonic distortion (THD) up to 5.65%. MATLAB Simulink results are included to demonstrate the effectiveness of the proposed multi-level inverter.